Pengaruh Video Animasi terhadap Pengetahuan tentang Pencegahan Skabies pada Anak Panti Rehabilitasi - Zahra Diba; Theresia Budi Lestari; Jesika Pasaribu (Universitas Malahayati Lampung, 2025)
ABSTRACT Skin infection scabies often occurs among individuals in densely populated environments with high interpersonal contact, such as rehabilitation centers housing children from correctional facilities. Scabies infection can be prevented with good personal and environmental hygiene practices. Adequate knowledge is crucial for the prevention and management of scabies infections. This study aims to analyze the influence of health promotion using animated video media in increasing the knowledge of rehabilitated children regarding the prevention and management of scabies. This study employs a pre-experimental design with a one-group Pre-test–Post-test approach. The study sample consisted of 50 respondents, selected using the total sampling technique. Research instruments included animated videos and a knowledge questionnaire. Data collection was conducted in June 2023, with a Pre-test administered before providing the animated video and a Post-test given after a 15-day interval. Data analysis was performed using the Wilcoxon test. The majority of respondents had a high school education or equivalent (54%). There was a significant increase in knowledge between the Pre-test (median: 16.50) and the Post-test (median: 19.00). The minimum Pre-test score rose from 2 to 11 in the Post-test. Bivariate analysis showed significant results, with a p-value of 0.000 (0.05). Animated videos are effective in increasing knowledge about scabies. This study is expected to serve as a media choice for health promotion related to scabies prevention. Keywords: Adolescents, Animated Video, Health Promotion, Scabies ABSTRAK Infeksi kulit skabies sering terjadi di lingkungan padat dengan kontak interpersonal tinggi, seperti panti rehabilitasi yang dihuni oleh anak-anak dari lembaga pemasyarakatan. Pencegahan infeksi skabies dapat dilakukan melalui praktik kebersihan diri dan lingkungan yang baik. Peningkatan pengetahuan tentang skabies sangat penting untuk mengurangi risiko dan penyebaran infeksi. Penelitian ini bertujuan untuk mengevaluasi pengaruh promosi kesehatan menggunakan video animasi dalam meningkatkan pengetahuan anak-anak di panti rehabilitasi tentang pencegahan dan penanganan skabies. Penelitian ini menggunakan desain Pre-Experimental dengan rancangan one group Pre-test–Post-test, melibatkan 50 responden yang dipilih secara total sampling. Data dikumpulkan pada Juni 2023 melalui Pre-testsebelum penayangan video animasi, dan Post-test dilakukan 15 hari setelah penayangan video animasi pada responden yang sama. Analisis data menggunakan uji Wilcoxon menunjukkan peningkatan pengetahuan yang signifikan, dari median 16,50 pada Pre-test menjadi 19,00 pada Post-test, dengan nilai p-value yang sangat signifikan (0,000). Penemuan ini menegaskan bahwa video animasi efektif sebagai alat untuk meningkatkan pemahaman tentang pencegahan skabies di kalangan anak-anak panti rehabilitasi. Kata Kunci: Promosi Kesehatan, Remaja, Skabies, Video Animasi